Simulation study of the effects of near‐ and far‐field heating during focused ultrasound uterine fibroid ablation using an electronically focused phased array: A theoretical analysis of patient safety. Issue 7 (20th June 2014) - Ellens, Nicholas; Hynynen, Kullervo
Abstract : Purpose: Assess the feasibility of using large‐aperture, flat ultrasonic transducer arrays with 6500 small elements operating at 500 kHz without the use of any mechanical components for the thermal coagulation of uterine fibroids. This study examines the benefits and detriments of using a frequency that is significantly lower than that used in clinical systems (1–1.5 MHz). Methods: Ultrasound simulations were performed using the anatomies of five fibroid patients derived from 3D MRI. Using electronic steering solely, the ultrasound focus from a flat, 6500‐element phased array was translated around the volume of the fibroids in various patterns to assess the feasibility of completing full treatments from fixed physical locations. Successive temperature maps were generated by numerically solving the bioheat equation. Using a thermal dose model, the bioeffects of these simulations were quantified and analyzed. Results: The simulations indicate that such an array could be used to perform fibroid treatments to 18 EM43 at an average rate of 90 ± 20 cm 3 /h without physically moving the transducer array. On average, the maximum near‐field thermal dose for each patient was below 4 EM43 . Fibroid tissue could be treated as close as 40 mm to the spine without reaching temperatures expected to cause pain or damage. Conclusions: Fibroids were successfully targeted and treated from a single transducer position to acceptable extents and without causing damage in the near‐ or far‐field. Compared to clinical systems, treatment rates were good. The proposed treatment paradigm is a promising alternative to existing systems and warrants further investigation.